Semi-solid-state high-heat-resistance lithium battery diaphragm and semi-solid-state lithium battery
By adopting a layered structure in the semi-solid lithium battery separator, nanocellulose coating and semi-solid inorganic material and hollow bonding material are arranged on both sides of the base film layer, the existing separator has poor heat shrinkability and insufficient liquid retention ability at high temperatures, and high heat resistance, strong adhesion and good liquid retention ability are achieved.
Patent Information
- Application Number
- CN202510149202.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing semi-solid lithium battery separators have poor thermal shrinkage at high temperatures, insufficient liquid retention capacity, and low adhesion to the electrode sheet, which cannot meet the performance needs of high-energy-density batteries.
A semi-solid high-heat-resistant lithium battery separator is adopted with a layered structure. Nanocellulose coating, a mixed coating of semi-solid inorganic materials and hollow bonding materials are provided on both sides of the base film layer in turn. This structural design improves the heat resistance, adhesion and liquid retention ability of the separator.
The separator has achieved good heat resistance, heat shrinkability and high breakdown voltage, enhanced adhesion with the electrode sheet, and improved the battery's circulation performance and liquid retention ability.
Smart Images

Figure CN119674452A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a semi-solid high-heat-resistant lithium ion battery separator, and also to a semi-solid lithium battery comprising the semi-solid high-heat-resistant lithium battery separator. Background Art
[0002] Lithium-ion batteries are widely used in various fields due to their excellent electrochemical properties such as high energy density and long cycle performance. The positive electrode, negative electrode, electrolyte and separator are the important components of lithium-ion batteries, among which the separator plays a key role in separating the positive and negative electrodes, insulating electrons and conducting lithium ions.
[0003] Semi-solid batteries are a transitional technology for solid-state batteries. The semi-solid lithium battery separators used are obtained by coating a layer of lithium-containing compounds on the surface of the base film. Among the lithium-containing compounds, LATP (lithium aluminum titanium phosphate) material has relatively stable performance, low cost, good ion conductivity, and the resistance of LATP coated separators is significantly lower than that of traditional ceramic coatings. Therefore, LATP coating materials are the main separator coating materials in the current semi-solid lithium battery market. At present, most semi-solid LATP separators on the market are prepared using a water-based formula of micron-level LATP materials. The LATP separator coatings have the following disadvantages: 1. The coating is relatively thick (about 3-5μm) and has poor thermal shrinkage (<5% at 130°C); 2. The adhesion between the separator and the electrode is low.
[0004] As the energy density of the battery cell increases, the thickness of the base film decreases accordingly, and the semi-solid coating is required to be thinner and thinner. These changes will lead to the poor liquid retention ability of the diaphragm, and it will not be able to withstand ultra-high temperatures, and the thermal shrinkage performance will also deteriorate. These problems need to be solved. At present, there are also attempts to prepare semi-solid LATP oily diaphragms, but the cost is high and it is not environmentally friendly.
[0005] Based on the above existing problems, the present invention aims to develop a semi-solid high heat-resistant lithium battery separator to meet the performance requirements of semi-solid batteries. Summary of the invention
[0006] The main technical problem solved by the present invention is to provide a semi-solid high heat-resistant lithium battery separator. At the same time, the present invention also provides a semi-solid lithium battery.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a semi-solid high heat-resistant lithium battery separator, the separator has a layered structure, including a base film layer, on one side of the base film layer, a first nano-cellulose coating, a semi-solid inorganic material and a hollow adhesive material mixed coating are sequentially arranged; on the other side of the base film layer, a second nano-cellulose coating, a semi-solid inorganic material coating, and a hollow adhesive material coating are sequentially arranged.
[0008] As an embodiment of the present invention, the base film layer is selected from PP (polypropylene), PE (polyethylene) or non-woven fabrics. The porosity of the base film is 25-70%.
[0009] As an embodiment of the present invention, the thickness of the base film layer is 1-20 μm. Further, the thickness of the base film layer is 2-10 μm.
[0010] As an embodiment of the present invention, the raw material for preparing the first nanocellulose coating includes at least one of nanocellulose microcrystals, methylcellulose, hydroxyethyl methylcellulose, carboxymethyl cellulose, ethyl cellulose, benzyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, cyanoethyl cellulose, benzyl cyanoethyl cellulose, carboxymethyl hydroxyethyl cellulose, and phenyl cellulose. The raw material for preparing the first nanocellulose coating has a diameter of 1-20 nm, a length of 0.01-10 μm, and a specific surface area of 8-100 g / m 2 .
[0011] As an embodiment of the present invention, the thickness of the first nanocellulose coating is 0.1-1 μm. Further, the thickness of the first nanocellulose coating is 0.5-1 μm.
[0012] As an embodiment of the present invention, when preparing the first nanocellulose coating, a coating liquid is first prepared, and then the first nanocellulose coating is coated. The coating liquid is prepared by mixing the raw materials (such as nanocellulose crystals) with water, then adding auxiliary materials, and stirring to obtain the coating liquid. The mass percentage concentration of the raw materials in the coating liquid is 25-35%. The auxiliary materials are at least one selected from dispersants, wetting agents, thickeners, and binders, and the mass percentage concentration of the auxiliary materials in the coating liquid is 2-5%. Preferably, the auxiliary materials are dispersants, wetting agents, thickeners, and binders.
[0013] As an embodiment of the present invention, the raw materials for preparing the mixed coating of the semi-solid inorganic material and the hollow bonding material include a semi-solid inorganic material and a hollow bonding material, and the semi-solid inorganic material and the hollow bonding material are mixed in a mass ratio of (5-10): 1. Further, the semi-solid inorganic material and the hollow bonding material are mixed in a mass ratio of (6-8): 1. For example, the semi-solid inorganic material and the hollow bonding material can be mixed in a mass ratio of 6:1, 7:1 or 8:1.
[0014] As an embodiment of the present invention, the thickness of the mixed coating of the semi-solid inorganic material and the hollow bonding material is 1-5 μm. Further, the thickness of the mixed coating of the semi-solid inorganic material and the hollow bonding material is 3-5 μm.
[0015] As an embodiment of the present invention, the semi-solid inorganic material is selected from at least one of LATP (lithium aluminum titanium phosphate) solid electrolyte, LAGP (lithium aluminum germanium phosphate) solid electrolyte, LLZO (lithium lanthanum zirconium oxide) solid electrolyte, LLTO (lithium lanthanum titanium oxide) solid electrolyte, alumina, boehmite, silicon dioxide, magnesium hydroxide, attapulgite, and mullite. The powder particle size of the semi-solid inorganic material is 0.01-5μm, and the specific surface area is 5-100g / m 2 .
[0016] As an embodiment of the present invention, the hollow bonding material is at least one hollow bonding material selected from polymethyl methacrylate (PMMA), polyvinylidene fluoride (such as polyvinylidene fluoride PVDF), and polyacrylic acid resin.
[0017] Furthermore, the powder particles of the hollow bonding material have a diameter of 0.1-10 μm and a wall thickness of 2-1000 nm.
[0018] As an embodiment of the present invention, when preparing the mixed coating of the semi-solid inorganic material and the hollow bonding material, a mixed coating coating liquid is first prepared, and then the mixed coating of the semi-solid inorganic material and the hollow bonding material is coated. The preparation method of the coating liquid is: the semi-solid inorganic material and the hollow bonding material are mixed with water, and then auxiliary materials are added and stirred to obtain the coating liquid. The total mass percentage concentration of the semi-solid inorganic material and the hollow bonding material in the coating liquid is 35-45%. For example, the total mass percentage concentration of the semi-solid inorganic material and the hollow bonding material in the coating liquid can be 35%, 36%, 37%, 40%, 41%, 43% or 45% and any other value within 35-45%. The auxiliary material is at least one selected from a dispersant, a wetting agent, a thickener, and a binder, and the mass percentage concentration of the auxiliary material in the coating liquid is 2-5%. Preferably, the auxiliary material is a dispersant, a wetting agent, a thickener and a binder.
[0019] As an embodiment of the present invention, the raw material for preparing the second nanocellulose coating includes at least one of nanocellulose microcrystals, methylcellulose, hydroxyethyl methylcellulose, carboxymethyl cellulose, ethyl cellulose, benzyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, cyanoethyl cellulose, benzyl cyanoethyl cellulose, carboxymethyl hydroxyethyl cellulose, and phenyl cellulose. The raw material for preparing the second nanocellulose coating has a diameter of 1-20 nm, a length of 0.01-10 μm, and a specific surface area of 8-100 g / m 2 .
[0020] As an embodiment of the present invention, the thickness of the second nanocellulose coating is 0.1-1 μm. Further, the thickness of the second nanocellulose coating is 0.5-1 μm.
[0021] As an embodiment of the present invention, when preparing the second nanocellulose coating, a coating liquid is first prepared, and then the second nanocellulose coating is coated. The coating liquid is prepared by mixing the raw materials (such as nanocellulose crystals) with water, then adding auxiliary materials, and stirring to obtain the coating liquid. The mass percentage concentration of the raw materials in the coating liquid is 25-35%. The auxiliary materials are at least one selected from dispersants, wetting agents, thickeners, and binders, and the mass percentage concentration of the auxiliary materials in the coating liquid is 2-5%. Preferably, the auxiliary materials are dispersants, wetting agents, thickeners, and binders.
[0022] As an embodiment of the present invention, the raw material for preparing the semi-solid inorganic material coating is selected from at least one of LATP (lithium aluminum titanium phosphate) solid electrolyte, LAGP (lithium aluminum germanium phosphate) solid electrolyte, LLZO (lithium lanthanum zirconium oxide) solid electrolyte, LLTO (lithium lanthanum titanium oxide) solid electrolyte, alumina, boehmite, silicon dioxide, magnesium hydroxide, attapulgite, and mullite. The powder particle size of the raw material for preparing the semi-solid inorganic material coating is 0.01-5μm, and the specific surface area is 5-100g / m 2 .
[0023] As an embodiment of the present invention, the thickness of the semi-solid inorganic material coating is 0.1-5 μm. Further, the thickness of the semi-solid inorganic material coating is 1-2 μm.
[0024] As an embodiment of the present invention, when preparing the semi-solid inorganic material coating, a coating coating liquid is first prepared, and then the semi-solid inorganic material coating is prepared by coating. The preparation method of the coating liquid is: the semi-solid inorganic material is mixed with water, and then auxiliary materials are added, and the coating liquid is obtained by stirring. The mass percentage concentration of the semi-solid inorganic material in the coating liquid is 35-45%. For example, the mass percentage concentration of the semi-solid inorganic material in the coating liquid can be 35%, 36%, 37%, 40%, 41%, 43% or 45% and any other value within 35-45%. The auxiliary material is at least one selected from a dispersant, a wetting agent, a thickener, and a binder, and the mass percentage concentration of the auxiliary material in the coating liquid is 2-5%. Preferably, the auxiliary material is a dispersant, a wetting agent, a thickener and a binder.
[0025] As an embodiment of the present invention, the raw material for preparing the hollow bonding material coating is selected from at least one hollow bonding material selected from polymethyl methacrylate (PMMA), polyvinylidene fluoride (such as polyvinylidene fluoride PVDF), and polyacrylic acid resin.
[0026] Furthermore, the powder particles of the hollow bonding material have a diameter of 0.1-10 μm and a wall thickness of 2-1000 nm.
[0027] As an embodiment of the present invention, the thickness of the hollow bonding material coating is 0.5-10 μm. Further, the thickness of the hollow bonding material coating is 0.5-1 μm.
[0028] As an embodiment of the present invention, when preparing the hollow adhesive material coating, a coating coating liquid is first prepared, and then the hollow adhesive material coating is coated. The preparation method of the coating liquid is: the hollow adhesive material is mixed with water, and then auxiliary materials are added and stirred to obtain the coating liquid. The mass percentage concentration of the hollow adhesive material in the coating liquid is 20-30%. For example, the mass percentage concentration of the hollow adhesive material in the coating liquid can be 20%, 22%, 24%, 24.5%, 25%, 28% or 30% and any other value within 20-30%. The auxiliary material is at least one selected from a dispersant, a wetting agent, a thickener, and a binder, and the mass percentage concentration of the auxiliary material in the coating liquid is 0.1-1.0%. Preferably, the auxiliary material is a wetting agent.
[0029] As an embodiment of the present invention, the thickness of the semi-solid high heat-resistant lithium battery separator is 10-20 μm.
[0030] The present invention also provides a semi-solid lithium battery, which includes the semi-solid high heat-resistant lithium battery separator provided by the present invention.
[0031] The semi-solid lithium battery separator provided by the present invention has different functional coatings on both sides of the base film layer. This double-sided different coating structure is designed according to the characteristics of the positive and negative electrodes. The nanocellulose coating has the advantages of high heat resistance, easy absorption of electrolyte, thin coating, etc.; the semi-solid inorganic material coating has the performance of heat resistance and high breakdown voltage; the hollow adhesive material coating can improve the bonding force between the separator and the electrode; the semi-solid inorganic material and hollow adhesive material mixed coating not only has a strong bonding force with the electrode, but also the hollow adhesive material in the coating is compressible, which provides a certain space for the expansion of the entire battery, thereby improving the battery cycle performance.
[0032] The semi-solid lithium battery diaphragm provided by the present invention has strong liquid retention capacity, good heat resistance, good heat shrinkage, high breakdown voltage, and strong bonding force between the diaphragm and the positive and negative electrode sheets. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the structure of the semi-solid lithium battery separator provided by Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is described in detail below through specific embodiments. The following embodiments are intended to further illustrate the content of the present invention in detail, but are not intended to limit the scope of protection of the claims of the present invention.
[0035] In the present invention, the auxiliary materials such as dispersants etc. used may be auxiliary materials commonly used in the field of lithium battery separator preparation.
[0036] Specifically, in the following embodiments and comparative examples: The dispersants used are all Shandong Zhitang DP03 quaternary ammonium salt; The wetting agents used are all polyether wetting agents, specifically Shandong Zhitang TW80 wetting agent; The thickeners used are sodium carboxymethyl cellulose; The adhesives used are all acrylic resin adhesives (Hunan Gaorui GR401).
[0037] The base film layer used is made of PP (polypropylene). The thickness of the base film layer is 5μm. The porosity of the base film is 38%.
[0038] The raw materials for preparing the first nanocellulose coating are the same as those for preparing the second nanocellulose coating, both of which are nanocellulose microcrystals. The diameter of the nanocellulose microcrystals is 4 nm, the length is 0.2 μm, and the specific surface area is 40 g / m 2 .
[0039] The raw materials for preparing the mixed coating of semi-solid inorganic material and hollow bonding material are semi-solid inorganic material and hollow bonding material. Among them, the semi-solid inorganic material is LATP (lithium aluminum titanium phosphate) solid electrolyte, the powder particle size is 0.5μm, and the specific surface area is 18g / m 2 The hollow bonding material is polymethyl methacrylate (PMMA) hollow bonding material, the powder particle diameter is 3 μm, and the wall thickness is 500 nm.
[0040] The raw material for preparing the semi-solid inorganic material coating is LATP (lithium aluminum titanium phosphate) solid electrolyte, the powder particle size is 0.5μm, and the specific surface area is 17g / m 2 .
[0041] The raw material for preparing the hollow bonding material coating is polymethyl methacrylate (PMMA) hollow bonding material, the powder particle diameter is 0.3 μm, and the wall thickness is 150 nm.
[0042] In the following examples and comparative examples, unless otherwise specified, all reagents used are commercially available products.
[0043] In the following examples and comparative examples, unless otherwise specified, the experimental methods used are conventional experimental methods.
[0044] Example 1 This embodiment provides a semi-solid lithium battery separator. Figure 1 As shown, it includes a base film layer 10, on one side of the base film layer 10, a first nano-cellulose coating 11 and a mixed coating 12 of a semi-solid inorganic material and a hollow adhesive material are sequentially arranged; on the other side of the base film layer 10, a second nano-cellulose coating 13, a semi-solid inorganic material coating 14, and a hollow adhesive material coating 15 are sequentially arranged.
[0045] The thickness of the base film layer 10 is 5 μm, the thickness of the first nanocellulose coating 11 is 0.5 μm, the thickness of the semi-solid inorganic material and hollow adhesive material mixed coating 12 is 3 μm, the thickness of the second nanocellulose coating 13 is 0.5 μm, the thickness of the semi-solid inorganic material coating 14 is 1 μm, and the thickness of the hollow adhesive material coating 15 is 1 μm. The total thickness of the semi-solid high heat-resistant lithium battery separator is 11 μm.
[0046] The preparation process of the semi-solid lithium battery separator provided in this embodiment is as follows: (1) coating one side of the base film layer 10 to prepare a first nanocellulose coating layer 11; Preparation of coating liquid: mixing nanocellulose microcrystals with deionized water, then adding auxiliary materials such as dispersant, wetting agent, thickener and binder, and stirring to prepare coating liquid; the weight parts of each component in the coating liquid are: 31 parts of nanocellulose microcrystals, 65 parts of deionized water, 0.5 parts of dispersant, 0.5 parts of wetting agent, 0.5 parts of thickener, and 2.5 parts of binder; Coating to prepare the first nanocellulose coating 11: using a micro-gravure device, coating the coating liquid on one side of the base film layer 10, and drying to prepare the first nanocellulose coating 11; (2) Coating a mixed coating 12 of a semi-solid inorganic material and a hollow bonding material on the first nanocellulose coating 11 Preparation of coating liquid: LATP solid electrolyte, PMMA hollow bonding material and deionized water are mixed, and then auxiliary materials such as dispersant, wetting agent, thickener and binder are added, and the coating liquid is prepared by stirring; the weight parts of each component in the coating liquid are: 35 parts of LATP solid electrolyte, 5 parts of PMMA hollow bonding material, 55 parts of deionized water, 0.5 parts of dispersant, 0.5 parts of wetting agent, 0.5 parts of thickener, and 3.5 parts of binder; Coating to prepare a mixed coating 12 of a semi-solid inorganic material and a hollow adhesive material: using a micro-gravure device, coating the coating liquid on the first nanocellulose coating 11, and drying to prepare a mixed coating 12 of a semi-solid inorganic material and a hollow adhesive material; (3) coating the other side of the base film layer 10 to prepare a second nanocellulose coating 13; Preparation of coating liquid: mixing nanocellulose microcrystals with deionized water, then adding auxiliary materials such as dispersant, wetting agent, thickener and binder, and stirring to prepare coating liquid; the weight parts of each component in the coating liquid are: 31 parts of nanocellulose microcrystals, 65 parts of deionized water, 0.5 parts of dispersant, 0.5 parts of wetting agent, 0.5 parts of thickener, and 2.5 parts of binder; Coating to prepare the second nanocellulose coating 13: using a micro-gravure device, coating the coating liquid on the other side of the base film layer 10, and drying to prepare the second nanocellulose coating 13; (4) coating the second nanocellulose coating 13 with a semi-solid inorganic material coating 14; Preparation of coating liquid: LATP solid electrolyte is mixed with deionized water, and then auxiliary materials such as dispersant, wetting agent, thickener and binder are added, and the coating liquid is prepared by stirring; the weight parts of each component in the coating liquid are: 40 parts of LATP solid electrolyte, 55 parts of deionized water, 0.5 parts of dispersant, 0.5 parts of wetting agent, 0.5 parts of thickener, and 3.5 parts of binder; Coating to prepare a semi-solid inorganic material coating 14: using a micro-gravure device, coating the coating liquid on the second nanocellulose coating 13, and drying to prepare a semi-solid inorganic material coating 14; (5) Coating a hollow bonding material coating 15 on the semi-solid inorganic material coating 14 Preparation of coating liquid: Mixing PMMA hollow bonding material with deionized water, then adding auxiliary material wetting agent, stirring to prepare coating liquid; the weight proportions of each component in the coating liquid are: 24.5 parts of PMMA hollow bonding material, 75 parts of deionized water, and 0.5 parts of wetting agent; Coating to prepare the hollow adhesive material coating 15: Use a micro-gravure device to coat the above coating liquid on the semi-solid inorganic material coating 14, and dry it to prepare the hollow adhesive material coating 15.
[0047] Through the above steps, the semi-solid lithium battery separator provided in this embodiment is prepared.
[0048] Example 2 This embodiment provides a semi-solid lithium battery separator. Figure 1 As shown, it includes a base film layer 10, on one side of the base film layer 10, a first nano-cellulose coating 11 and a mixed coating 12 of a semi-solid inorganic material and a hollow adhesive material are sequentially arranged; on the other side of the base film layer 10, a second nano-cellulose coating 13, a semi-solid inorganic material coating 14, and a hollow adhesive material coating 15 are sequentially arranged.
[0049] The thickness of the base film layer 10 is 5 μm, the thickness of the first nanocellulose coating 11 is 1 μm, the thickness of the semi-solid inorganic material and hollow adhesive material mixed coating 12 is 5 μm, the thickness of the second nanocellulose coating 13 is 1 μm, the thickness of the semi-solid inorganic material coating 14 is 2 μm, and the thickness of the hollow adhesive material coating 15 is 1 μm. The total thickness of the semi-solid high heat-resistant lithium battery separator is 15 μm.
[0050] The preparation process of the semi-solid lithium battery separator provided in this embodiment refers to Example 1, and the coating liquid used in each coating is the same as that in Example 1, and the only difference is that the thickness of the prepared coating is different from that in Example 1.
[0051] Example 3 This embodiment provides a semi-solid lithium battery separator. Figure 1 As shown, it includes a base film layer 10, on one side of the base film layer 10, a first nano-cellulose coating 11 and a mixed coating 12 of a semi-solid inorganic material and a hollow adhesive material are sequentially arranged; on the other side of the base film layer 10, a second nano-cellulose coating 13, a semi-solid inorganic material coating 14, and a hollow adhesive material coating 15 are sequentially arranged.
[0052] The thickness of the base film layer 10 is 5 μm, the thickness of the first nanocellulose coating 11 is 0.5 μm, the thickness of the semi-solid inorganic material and hollow adhesive material mixed coating 12 is 5 μm, the thickness of the second nanocellulose coating 13 is 0.5 μm, the thickness of the semi-solid inorganic material coating 14 is 1 μm, and the thickness of the hollow adhesive material coating 15 is 0.5 μm. The total thickness of the semi-solid high heat-resistant lithium battery separator is 12.5 μm.
[0053] The preparation process of the semi-solid lithium battery separator provided in this embodiment refers to Example 1, and the coating liquid used in each coating is the same as that in Example 1, and the only difference is that the thickness of the prepared coating is different from that in Example 1.
[0054] Example 4 This embodiment provides a semi-solid lithium battery separator. Figure 1 As shown, it includes a base film layer 10, on one side of the base film layer 10, a first nano-cellulose coating 11 and a mixed coating 12 of a semi-solid inorganic material and a hollow adhesive material are sequentially arranged; on the other side of the base film layer 10, a second nano-cellulose coating 13, a semi-solid inorganic material coating 14, and a hollow adhesive material coating 15 are sequentially arranged.
[0055] The thickness of the base film layer 10 is 5 μm, the thickness of the first nanocellulose coating 11 is 1 μm, the thickness of the semi-solid inorganic material and hollow adhesive material mixed coating 12 is 3 μm, the thickness of the second nanocellulose coating 13 is 0.5 μm, the thickness of the semi-solid inorganic material coating 14 is 2 μm, and the thickness of the hollow adhesive material coating 15 is 1 μm. The total thickness of the semi-solid high heat-resistant lithium battery separator is 12.5 μm.
[0056] The preparation process of the semi-solid lithium battery separator provided in this embodiment refers to Example 1, and the coating liquid used in each coating is the same as that in Example 1, and the only difference is that the thickness of the prepared coating is different from that in Example 1.
[0057] Comparative Example 1 This comparative example provides a semi-solid lithium battery separator, including a base film layer, and semi-solid inorganic material coatings are coated on both sides of the base film layer, wherein the base film layer has a thickness of 5 μm, and the thickness of the semi-solid inorganic material coatings on both sides is 2 μm.
[0058] The weight proportion of the coating liquid of the semi-solid inorganic material coating is as follows: 31 parts of LATP solid electrolyte, 65 parts of deionized water, 0.5 parts of dispersant, 0.5 parts of wetting agent, 1 part of thickener, and 2 parts of binder.
[0059] Preparation of coating liquid: Mix LATP solid electrolyte with deionized water, then add auxiliary materials such as dispersant, wetting agent, thickener and binder, and stir to obtain coating liquid.
[0060] The coating liquid is coated on both sides of the base film layer by using a micro-gravure device, and then dried to prepare a semi-solid lithium battery separator.
[0061] The performance of the semi-solid lithium battery separators prepared in the above Examples 1-4 and Comparative Example 1 was tested, and the results are shown in Table 1 below.
[0062] The bonding strength test method is as follows: place the battery pole piece and the lithium battery separator on a flat hot press, hot press for 60 seconds at a temperature of 90°C and a pressure of 3 MPa, then take them out and test the bonding strength between the separator and the pole piece on a tensile testing machine; Thermal shrinkage performance test: measure the length and width of the lithium battery separator sample, then place it in a blast oven at 180°C for 1 hour, take it out, and then measure the length and width of the lithium battery separator sample after heating, and calculate the thermal shrinkage rate; Detection of breakdown voltage: Use a diaphragm voltage tester to test and record the voltage when the diaphragm is broken down; Detection of liquid retention: measure the weight of the lithium battery diaphragm sample, then soak the lithium battery diaphragm sample in the electrolyte for 0.5h, take it out, and then measure the weight of the lithium battery diaphragm sample at this time, and calculate the liquid retention. The calculation formula is: (weight of the lithium battery diaphragm sample after immersion - weight of the lithium battery diaphragm sample before immersion) / area of the lithium battery diaphragm sample.
[0063] Table 1 Detection object Adhesion force between diaphragm and battery pole piece N / m 180℃ / 1h Thermal shrinkage / % Breakdown voltage / V <![CDATA[Liquid retention amount g / m 2 > Comparative Example 1 0 / 0 MD=20%TD=25% 82 / 95 / 79 53 Example 1 5 / 7 MD=4.2%TD=3.2% 165 / 170 / 150 70 Example 2 12 / 15 MD=3%TD=3.5% 123 / 116 / 134 92 Example 3 7 / 10 MD=4.5%TD=4.7% 195 / 207 / 188 67 Example 4 5 / 8 MD=2.5%TD=2.3% 174 / 168 / 179 80 It should be noted that, taking Example 1 as an example, the data "5 / 7" of the adhesion between the diaphragm and the battery pole piece in Table 1, the front "5" is the adhesion between the side of the semi-solid inorganic material and hollow adhesive material mixed coating 12 and the battery pole piece, and the back "7" is the adhesion between the side of the hollow adhesive material coating 15 and the battery pole piece. The adhesion data between the diaphragm and the battery pole piece of other embodiments are the same as those of Example 1.
[0064] It can be seen from the data in Table 1 that the semi-solid lithium battery separator provided by Examples 1-4 of the present invention has a stronger liquid retention capacity than the existing common semi-solid lithium battery separator provided by Comparative Example 1; it has good heat resistance and good thermal shrinkage; the breakdown voltage is significantly improved; and the bonding force between the separator and the positive and negative electrodes of the battery is also significantly enhanced.
[0065] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A semi-solid high heat-resistant lithium battery separator, characterized in that: The diaphragm has a layered structure, including a base membrane layer, on one side of which a first nanocellulose coating, a semi-solid inorganic material and a hollow adhesive material mixed coating are sequentially arranged; on the other side of the base membrane layer, a second nanocellulose coating, a semi-solid inorganic material coating, and a hollow adhesive material coating are sequentially arranged.
2. The semi-solid high heat-resistant lithium battery separator according to claim 1, characterized in that: The base film layer is selected from PP, PE or non-woven fabric, and the thickness of the base film layer is 1-20 μm.
3. The semi-solid high heat-resistant lithium battery separator according to claim 1, characterized in that: The raw materials for preparing the first nanocellulose coating include at least one of nanocellulose microcrystals, methyl cellulose, hydroxyethyl methyl cellulose, carboxymethyl cellulose, ethyl cellulose, benzyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, cyanoethyl cellulose, benzyl cyanoethyl cellulose, carboxymethyl hydroxyethyl cellulose, and phenyl cellulose; the thickness of the first nanocellulose coating is 0.1-1 μm.
4. The semi-solid high heat-resistant lithium battery separator according to claim 1, characterized in that: The raw materials for preparing the mixed coating of the semi-solid inorganic material and the hollow bonding material include a semi-solid inorganic material and a hollow bonding material, and the semi-solid inorganic material and the hollow bonding material are mixed in a mass ratio of (5-10):1; the thickness of the mixed coating of the semi-solid inorganic material and the hollow bonding material is 1-5 μm; Wherein, the semi-solid inorganic material is selected from at least one of LATP, LAGP, LLZO, LLTO, alumina, boehmite, silicon dioxide, magnesium hydroxide, attapulgite, and mullite; The hollow bonding material is selected from at least one of polymethyl methacrylate, polyvinylidene fluoride and polyacrylic acid resin; the powder particle diameter of the hollow bonding material is 0.1-10 μm and the wall thickness is 2-1000 nm.
5. The semi-solid high heat-resistant lithium battery separator according to claim 1, characterized in that: The raw materials for preparing the second nanocellulose coating include at least one of nanocellulose microcrystals, methyl cellulose, hydroxyethyl methyl cellulose, carboxymethyl cellulose, ethyl cellulose, benzyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, cyanoethyl cellulose, benzyl cyanoethyl cellulose, carboxymethyl hydroxyethyl cellulose, and phenyl cellulose; the thickness of the second nanocellulose coating is 0.1-1 μm.
6. The semi-solid high heat-resistant lithium battery separator according to claim 1, characterized in that: The raw materials for preparing the semi-solid inorganic material coating include at least one of LATP, LAGP, LLZO, LLTO, alumina, boehmite, silicon dioxide, magnesium hydroxide, attapulgite and mullite; the thickness of the semi-solid inorganic material coating is 0.1-5 μm.
7. The semi-solid high heat-resistant lithium battery separator according to claim 1, characterized in that: The raw material for preparing the hollow adhesive material coating is selected from at least one hollow adhesive material of polymethyl methacrylate, polyvinylidene fluoride, and polyacrylic acid resin; the thickness of the hollow adhesive material coating is 0.5-10μm; the powder particle diameter of the raw material for preparing the hollow adhesive material coating is 0.1-10μm, and the wall thickness is 2-1000nm.
8. The semi-solid high heat-resistant lithium battery separator according to any one of claims 1 to 7, characterized in that: The semi-solid high heat-resistant lithium battery separator meets at least one of the following conditions (1)-(6): (1) The thickness of the base film layer is 2-10 μm; (2) The thickness of the first nanocellulose coating is 0.5-1 μm; (3) The thickness of the mixed coating of the semi-solid inorganic material and the hollow bonding material is 3-5 μm; (4) The thickness of the second nanocellulose coating is 0.5-1 μm; (5) The thickness of the semi-solid inorganic material coating is 1-2 μm; (6) The thickness of the hollow bonding material coating is 0.5-1 μm.
9. The semi-solid high heat-resistant lithium battery separator according to any one of claims 1 to 8, characterized in that: The thickness of the semi-solid high heat-resistant lithium battery separator is 10-20 μm.
10. A semi-solid lithium battery, characterized in that: A semi-solid high heat-resistant lithium battery separator comprising any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing binder nanometer material with hollow structure and application of binder nanometer material
CN116003713A
Diaphragm and preparation method and application thereof
CN116646682A
Diaphragm of semi-solid battery and preparation method of diaphragm
CN116937067A
Diaphragm, electrode assembly, battery and electric device
CN118676535A